2022
DOI: 10.1155/2022/3347303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Network Externalities and Recycling Channels on Closed-loop Supply Chain Operation Incorporating Consumers’ Dual Preferences

Abstract: Consumers’ awareness of environmental protection is gradually strengthened, and they often consider environmental protection characteristics of products during purchasing products. Based on the characteristic of consumers’ dual preferences for product quality and environmental friendliness, this paper constructs a novel closed-loop supply chain with network externalities for new products and remanufactured products under different waste product recycling channel strategies. It discusses the influence of produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…For instance, Zhou et al [8] introduced the theory of network externality to explore the impact of government subsidy with or without budget constraint on OEM decision making. Xie et al [27] examined the impact of network externality on CLSC members decision making with different waste recycling channel strategies considering consumers' dual preference for product quality and environmental friendliness. They found that the demands of both new and remanufactured products with network externalities are greater than those of products without network externalities.…”
Section: Network Externality In Scsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Zhou et al [8] introduced the theory of network externality to explore the impact of government subsidy with or without budget constraint on OEM decision making. Xie et al [27] examined the impact of network externality on CLSC members decision making with different waste recycling channel strategies considering consumers' dual preference for product quality and environmental friendliness. They found that the demands of both new and remanufactured products with network externalities are greater than those of products without network externalities.…”
Section: Network Externality In Scsmentioning
confidence: 99%
“…However, the above works consider network externality in the traditional supply chain, and few studies focus on the network externality characteristic of remanufactured products, except for Zhou et al [8] and Xie et al [27]. Differing from the above-mentioned studies, our paper examines the problems of CLSC members' optimal differential pricing and sales effort decisions considering the network externality of remanufactured product.…”
Section: Network Externality In Scsmentioning
confidence: 99%
“…For example, Zhou and Yuen [8] incorporated the network externality of remanufactured product into the model, and examined the optimal strategies for the OEM and the government. Xie et al [32] analyzed enterprises' optimal de-cisions with different used-product recycling channels based on consumers' dual preference for product quality and environmental friendliness and network externality for new and remanufactured products. However, except for Zhou et al [8] and Xie et al [32], the above research focuses on network externality of the traditional product, and few works focus on the network externality of remanufactured products.…”
Section: Network Externality In Scsmentioning
confidence: 99%
“…Xie et al [32] analyzed enterprises' optimal de-cisions with different used-product recycling channels based on consumers' dual preference for product quality and environmental friendliness and network externality for new and remanufactured products. However, except for Zhou et al [8] and Xie et al [32], the above research focuses on network externality of the traditional product, and few works focus on the network externality of remanufactured products. Differently from the aforementioned studies, our paper explores CLSC members' optimal strategies incorporating the network externality of remanufactured products into the research framework.…”
Section: Network Externality In Scsmentioning
confidence: 99%
“…Using classical game theory to solve supply chain problems is very common [36], and most of the supply chain participants in these studies are completely rational [20,37]. However, in reality, the game participants are often bounded rational [38].…”
Section: Literature Reviewmentioning
confidence: 99%